Energy Storage: Advances in Interfaces between Li Metal Anode and Electrolyte (Adv. Mater. Interfaces 2/2018). Issue 2 (24th January 2018) - Zhang, Xue‐Qiang; Cheng, Xin‐Bing; Zhang, Qiang
Abstract : Mimicking the Nüwa repairing the Pillar of Heaven in ancient Chinese mythology, the solid electrolyte interfaces is expected to be complete. In article number1701097, Qiang Zhang and co‐workers reviewed the interfacial science and engineering of Li metal anode and electrolyte to present design principles in constructing robust interface to stabilize Li metal anode in a working battery.